DIAGNOSIS KOMUNITAS UPAYA PENURUNAN KASUS HIPERTENSI PADA MASYARAKAT DESA KRESEK, KABUPATEN TANGERANG - Ananda, Muh. Pramudya; Drew, Clement (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2024)
Background: Hypertension is a condition where the systolic and diastolic blood pressure is ? 140 and/ or ? 90 mmHg. WHO stated that 1 billion people in the world suffer from hypertension, of which 20-35% occur in adults. Hypertension cases in developing countries will continue to increase and it is estimated that around 639 million cases in 2000 will become 1.15 billion cases in 2025 with an increase of around 80%. Based on Riskesdas 2018, the prevalence of hypertension in Banten Province is 29.47%. The incidence of hypertension cases in Kresek Community Health Center has increased quite significantly in the period July – September 2023, namely around 2,169 visits with the largest increase in cases coming from Kresek Village. Objective: Increase public knowledge about hypertension. Method: The community diagnosis method uses the Blum Paradigm and data collection is carried out throughmini survey. Problem priority is determined using the Delphi non-scoring method. The root cause of the problem is done with a diagramfishbone. Data on intervention results were obtained from questionnairespre-test andpost-test. Monitoring is carried out with PDCACycle and systems approach. Results: The results of the counseling showed that ? 70% of participants got a scorepost-test ? 70 and 30 participants were obtained with the result that 1 participant were able to perform antihypertensive exercise movements properly and correctly. Conclusion: The community diagnosis approach implemented was able to increase community knowledge about hypertension.